2022
DOI: 10.13080/z-a.2022.109.048
|View full text |Cite
|
Sign up to set email alerts
|

Induction and analysis of polyploids in daylily (Hemerocallis L.) plants

Abstract: Daylily (Hemerocallis L.) is a popular herbaceous perennial ornamental plant. The American Hemerocallis Society (AHS) currently has over 96,000 cultivars registered. Of these, half are tetraploids (4x), and the other half are diploids (2x). To enrich the breeding lines of tetraploid daylilies, colchicine is the most widely used. During the experiment, oryzalin (ORZ) and colchicine (CLC) were used for the polyploidisation of daylilies. Germinating seeds derived from diploid and tetraploid daylily cultivars as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Examination of daylily ploidy showed the occurrence of triploids or pentaploids [53]. Such polyploids are induced by antimitotic agents [53] or by misinterpreting ploidy levels during registration [54]. This shows uncommon phenomena in plants of triploid existence and even the possibility of mating.…”
Section: Ploidy In Breeding Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of daylily ploidy showed the occurrence of triploids or pentaploids [53]. Such polyploids are induced by antimitotic agents [53] or by misinterpreting ploidy levels during registration [54]. This shows uncommon phenomena in plants of triploid existence and even the possibility of mating.…”
Section: Ploidy In Breeding Programsmentioning
confidence: 99%
“…Examination of daylily ploidy showed the occurrence of triploids or pentaploids [53]. Such polyploids are induced by antimitotic agents [53] or by misinterpreting ploidy levels during registration [54].…”
Section: Ploidy In Breeding Programsmentioning
confidence: 99%
“…Tetraploid genotypes generally adapt better to water shortage conditions than diploid plants and exhibit larger stomata, higher chlorophyll content, and higher photosynthetic capacity, resulting in a competitive advantage under water-limited conditions [26][27][28]. A previous study with daylily polyploid induction by Misiukevičius and Stanys [29] showed that higher ploidy daylily plants had longer stomata.…”
Section: Ploidy Level Affects Plant Morphological and Photosynthetic ...mentioning
confidence: 99%
“…Nearly 99 thousand daylily cultivars are registered by the American Hemerocallis Society [30]. Daylilies naturally occur only as diploids and triploids [31]. One of the common ways to make plants more resistant to biotic and abiotic stresses is whole genome duplication (WGD) [19,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…One of the common ways to make plants more resistant to biotic and abiotic stresses is whole genome duplication (WGD) [19,32,33]. Tetraploid daylilies were artificially induced by using chemical antimitotic agents [34][35][36][37][38]. Currently, hybridizers focus on tetraploid daylily breeding programs with 69.8% of newly registered cultivars in the last five years being tetraploids [30].…”
Section: Introductionmentioning
confidence: 99%